PENYULUHAN TENTANG TATA KELOLA DAN PERRTANGGUNGJAWABAN DANA DESA DI DESA LABULIA KECAMATAN JONGGAT KABUPATEN LOMBOK TENGAH - satarudin - satarudin; Mohammad Huzaini; Jalaludin (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2022)
Law Number 6 of 2014 and its implementation regulation have mandated a more independent village government in managing its governanceand the various village’s natural resources, including assets and financial management. The counseling on managing and accountability village funds in Labulia village, Jonggat district, Central Lombok Regency, aims to 1). Increase the village officials' knowledge and understanding of the village funds or financial management, including planning and implementation stages; 2). Improve the village officials' technical accounting skills, especially the village fund or financial management unit, including the village financial reporting and administration.In conclusion, the community service program is very beneficial because it is following the village’s needs, such as managing the village funds, especially those sourced from central funds or APBN. Also, its material fits the village’s demand perfectly within the governance, accountability, and the village funds reporting, especially those sourced from the APBN.Technically, it is very communicative and interactive because it can involve participants actively in presenting the material.